(untitled) (Bangladesh Journal of Agriculture, 2023)
A laboratory experiment was conducted at the Department of Soil Science of Bangladesh Agricultural University, Mymensingh to assess the effect of cyanobacteria on soil properties of cultivated and forest lands of Madhupur Tract. The population of cyanobacteria in two soils from Madhupur and one fromfrom BAU farm was counted followed by their identification up to genera level by fluorescence microscope. A marked variation was observed in cyanobacterial population among the soils: 27.8x105 g-1 in BAU farm soil, 2.70x105 g-1 in Madhupur cultivated soil and 1.62x105 g-1 in Madhupur forest soil. A total of 21 isolates were identified from all the soils taking eight isolates from each of Madhupur cultivated and BAU farm soils, and five from Madhupur forest soil . Of the 21 isolates, six isolates taking two from each soil were inoculated into all the three soils to see their effect on soil properties. These were Fischerella Mc and Aulosira Mc from Madhurpur cultivated soil; Calothrix Mf and Scytonema Mf from Madhurpur forest soil; Anabaena Bf and Nostoc Bf from BAU farm soil. The results reveal that there was an increase of soil pH, organic matter, total N, available P, exchangeable Ca, available S and CEC and a decrease in exchangeable K and exchangeable Na concentrations. The impact of different isolates on most of the soil properties was significant except their effect on exchangeable K for all soils, exchangeable Na for BAU farm soil and CEC for Madhurpur cultivated soil. Usually isolates showed better performance in their native soils than in other soils and cyanobacteria inoculation showed a positive indication towards improving fertility of soils. Bangladesh J. Agri. 2023, 48(1): 112-122